2017
DOI: 10.1186/s12887-017-0916-7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of rotavirus vaccines against hospitalisations in Japan

Abstract: BackgroundIn Japan, rotavirus hospitalisation occurs at a rate from 2.8 to 13.7 per 1000 child-years among children age less than 5 years, and it imposes a substantial burden to the healthcare system in the country. While both monovalent (RV1) and pentavalent (RV5) rotavirus vaccines are licensed in Japan, neither has been incorporated in the national infant immunization programme. In this study, we estimated vaccine effectiveness (VE) in Japan.MethodsThis study was conducted in Yuri-Kumiai General Hospital lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 22 publications
2
12
1
Order By: Relevance
“…The VE against severe RVGE requiring hospitalization was calculated as 70.4% in that study. 19 The estimate of VE (86.6% [95% CI, 55.9–96.0]) in our present study was higher than previous studies in Japan, although the confidence interval overlaps those of previous studies, as well as those from other developed countries. 2022…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The VE against severe RVGE requiring hospitalization was calculated as 70.4% in that study. 19 The estimate of VE (86.6% [95% CI, 55.9–96.0]) in our present study was higher than previous studies in Japan, although the confidence interval overlaps those of previous studies, as well as those from other developed countries. 2022…”
Section: Discussionsupporting
confidence: 58%
“…To date, to the best of our knowledge, there are only two studies that evaluated rotavirus vaccine effectiveness in Japan. 18 , 19 One is our own previous case-population study in Saga Prefecture, which reported a 69.5% VE against RVGE and 88.8% VE against severe RVGE requiring hospitalization. 18 That study was important for monitoring VE; it was the first on VE undertaken shortly after introduction of the rotavirus vaccines.…”
Section: Discussionmentioning
confidence: 95%
“…In Asia, few countries have introduced RVV. Earlier results from high income countries of Asia in Hong Kong 7 and Japan 8 , where RVV are self-financed, revealed RVV effectiveness of 89% and 70%, respectively against diarrheal hospitalization. However, a cluster-randomized study conducted in Bangladesh, a low income country, revealed that the monovalent RVV effectiveness was 41.4% 9 .…”
Section: Introductionmentioning
confidence: 98%
“…Three studies from China reported vaccine effectiveness estimates ranging between 35%-44.6% against RVGE cases [32][33][34] and one study reported vaccine effectiveness of 74.5% against RVGE hospitalization [33]. Data from Japan reported vaccine effectiveness estimates ranging from 70.4%-97.3% against RVGE requiring hospitalization [35][36][37]. A study from Australia, reported a vaccine effectiveness of 84.5% against RVGE hospitalization [38].…”
Section: Overview Of Rotavirus Vaccination Implementation In the Regionmentioning
confidence: 99%